Effectiveness of teaching methods and motor abilities: an experimental study on football passing ability - Arsil, Arsil; Suryadi, Didi; Antoni, Despita; Suganda, Mikkey Anggara; Okilanda, Ardo; Rozi, Muhammad Fakhrur; Saputra, Mardepi; Mortezo, Alonzo L (Retos (Madrid), 2024)
The low score of football passing ability among students is a problem in this topic. Therefore, efforts to improve the quality of the learning process are an effort to increase students' mastery of football passing abilities through teaching methods of philanesia and parts by first looking at students' motor skills. This research aims to determine the effectiveness of teaching methods and motor skills on passing ability in soccer games. The design used in this research is an experimental method using a 2x2 factorial design. The research subjects were FIK UNP students, using a cluster random sampling technique so that 24 students were sampled. Next, data analysis was assisted using the SPSS 26 application. The research results showed that the overall method and motor skills provided a significance value (0.000 < 0.05). Furthermore, the philanesia method and motor skills provide significance values (0.013 < 0.05). The results of the ANOVA test show a significance of 0.001 < 0.05. This data proves that there is a significant difference in the influence of the overall method and the philanesia method with low and high motor skills on the results of soccer passing ability. Based on these results, it can be concluded that both the overall method and the philanesia method with motor skills provide significant effectiveness in improving students' soccer passing ability. However, the football passing ability of the group of students who were opened using the overall method produced better results than the group of students who were opened using the philanesia method. La baja puntuación de la capacidad de pase de fútbol entre los estudiantes es un problema en este tema. Por lo tanto, los esfuerzos para mejorar la calidad del proceso de aprendizaje son un esfuerzo para aumentar el dominio de los estudiantes de las habilidades de pase de fútbol a través de métodos de enseñanza de philanesia y partes observando primero las habilidades motoras de los estudiantes. Esta investigación tiene como objetivo determinar la efectividad de los métodos de enseñanza y habilidades motoras sobre la capacidad de pase en los partidos de fútbol. El diseño utilizado en esta investigación es un método experimental utilizando un diseño factorial 2x2. Los sujetos de investigación fueron estudiantes de FIK UNP, utilizándose una técnica de muestreo aleatorio por conglomerados por lo que se muestreó a 24 estudiantes. A continuación, se asistió al análisis de los datos mediante la aplicación SPSS 26. Los resultados de la investigación mostraron que el método general y las habilidades motoras proporcionaron un valor significativo (0,000 <0,05). Además, el método filanesio y la motricidad aportan valores de significancia (0,013 < 0,05). Los resultados de la prueba ANOVA muestran una significación de 0,001 < 0,05. Estos datos demuestran que existe una diferencia significativa en la influencia del método general y el método filanesio con habilidades motoras altas y bajas en los resultados de la capacidad de pase en el fútbol. Con base en estos resultados, se puede concluir que tanto el método general como el método filanesio con habilidades motoras brindan una efectividad significativa en la mejora de la capacidad de pase de fútbol de los estudiantes. Sin embargo, la capacidad de pase de fútbol del grupo de estudiantes que fueron abiertos usando el método general produjo mejores resultados que el grupo de estudiantes que fueron abiertos usando el método filanesio.